Cultures of Anyone : Studies on Cultural Democratization in the Spanish Neoliberal Crisis. - Moreno-Caballud, Luis. (Contemporary Hispanic and Lusophone Cultures Series, 2015)
This book focuses on the rise of sharing and collaboration practices among peers in Spanish digital cultures and social movements in the wake of Spain's financial meltdown of 2008.